2013
DOI: 10.1364/boe.4.001045
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-optic OCT sensor guided “SMART” micro-forceps for microsurgery

Abstract: A handheld Smart Micromanipulation Aided Robotic-surgery Tool (SMART) micro-forceps guided by a fiber-optic common-path optical coherence tomography (CP-OCT) sensor is presented. A fiber-optic CP-OCT distance and motion sensor is integrated into the shaft of a micro-forceps. The tool tip position is manipulated longitudinally through a closed loop control using a piezoelectric motor. This novel forceps design could significantly enhance safety, efficiency and surgical outcomes. The basic grasping and peeling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 11 publications
0
36
1
1
Order By: Relevance
“…The Kang group at Johns Hopkins University demonstrated that Ascans could be acquired adjacent to the tooltip by mounting a fiber-optic common-path (CP) OCT probe along [107,108] or within [109][110][111] the shafts of forceps and needles for vitreoretinal surgery (Fig. 3(a)).…”
Section: Oct-integrated Surgical Instrumentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Kang group at Johns Hopkins University demonstrated that Ascans could be acquired adjacent to the tooltip by mounting a fiber-optic common-path (CP) OCT probe along [107,108] or within [109][110][111] the shafts of forceps and needles for vitreoretinal surgery (Fig. 3(a)).…”
Section: Oct-integrated Surgical Instrumentsmentioning
confidence: 99%
“…In its most recent iteration [108], the probe used a 100 kHz swept-source with a 1060 nm central wavelength, and M-scan images could be acquired and processed with GPU-accelerated software. The OCT probe was primarily used as a single-point axial ranger with micrometer-scale resolution to quantify hand tremor [111] and drive active motion cancellation systems [107,108,110], and to provide ranging feedback for a cooperative robotic surgery platform [109] (discussed in detail in Section 5.2). The Joos group at Vanderbilt University incorporated a needle-based OCT probe [105] capable of Bscan imaging into the shaft of 23-gauge surgical forceps [112] (Fig.…”
Section: Oct-integrated Surgical Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research group has established a potential role for a real-time OCT intraoperative guidance system with fast computational speed using a graphic processing unit (GPU) that is forward viewing and incorporated into the actual handheld tools [24][25][26][27][28][29][30][31][32][33][34][35]. Unlike typical OCT imaging, this application uses OCT as a distal sensor and its potential effectiveness for ocular microsurgery has been demonstrated [29][30][31][32][33][34][35]. The motion compensation that is based on the feedback from the OCT distal sensor effectively suppresses undesired axial motion; as a result, the frequency region related to hand tremor is significantly decreased [34].…”
Section: Introductionmentioning
confidence: 99%